Assessment of the impact of noise pollution on human health in Uguaja sawmill, Sapele Local Government Area - Isaac Omonigho Oyaigbevwen (African Research Reports, 2026)
This study assessed the impact of noise pollution on human health in the Uguaja sawmill, Sapele Local Government Area, Delta State. Specifically, it examined residents' awareness of noise pollution levels, assessed the behavior of sawmill management regarding the monitoring and control of noise generated by sawmill operations, and evaluated the effects of noise pollution on residents and workers. A descriptive survey design was adopted, and a sample of 100 respondents was selected from a target population of 1,000 using simple and stratified random sampling techniques. Data were collected using a self-designed questionnaire, and the chi-square (χ²) statistical test was used for data analysis. The findings revealed that noise pollution has significant adverse effects on the health of residents and sawmill workers and that the government plays a limited role in monitoring and controlling noise from sawmill operations. Based on these findings, it is recommended that adequate noise monitoring and assessment procedures be established, sawmill workers and residents be trained in modern safety practices, and sawmill management ensures the adequate provision and use of personal protective equipment (PPE) for all workers.